Design of Cognitive Conflict-Based Teaching Materials Integrating Real Experiment Video Analysis on Momentum and Impulse Materials to Improve Students' Concept Understanding - Reni Defrianti; Fatni Mufit; - Gusnedi; Zaitul Hidayat (PILLAR OF PHYSICS EDUCATION, 2021)
Students do not understand concepts and misconceptions occur in momentum and impulses. Less available teaching materials that can remediate misconceptions. This study aims to design cognitive conflict-based teaching materials that integrate video analysis of real experiments to improve students' conceptual understanding of momentum and impulses. This research is a development research using the Plomp model. In the preliminary research, journal analysis, interviews with physics teachers, and literature studies were conducted. At the prototyping stage, teaching materials are designed, self-evaluation is carried out, validation by 3 lecturers and one-to-one practicality test for 3 students. The data analysis technique used descriptive analysis for interviews, the Aiken-V formula for validation and percentage techniques for practicality tests. The results of the preliminary research, it was found that students' understanding of concepts was low and there were still misconceptions, the unavailability of teaching materials that corrected misconceptions. The results of the prototyping stage, momentum and impulse teaching materials were designed based on four syntaxes of cognitive conflict-based learning model (CCBL Model). In the third syntax, real-experiment video analysis is integrated using the tracker program. The results of the self-evaluation showed that the teaching materials were complete with very good criteria. The results of the validation test obtained a very valid value of 0.81. The results of the practicality test obtained a very practical value of 90.27. So, the design of cognitive conflict-based teaching materials integrating video analysis of real experiments on momentum and impulses is very valid and practical in one-on-one evaluation